2013
DOI: 10.1186/1471-2164-14-401
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics and expression profiles of the mitochondrial genome for the Mediterranean species of the Bemisia tabaci complex

Abstract: BackgroundThe whiteflies under the name Bemisia tabaci (Gennadius) (Aleyrodidae: Hemiptera) are species complex of at least 31 cryptic species some of which are globally invasive agricultural pests. Previously, the mitochondrial genome (mitogenome) of the indigenous New World B. tabaci species was sequenced and major differences of gene order from the postulated whitefly ancestral gene order were found. However, the sequence and gene order of mitogenomes in other B. tabaci species are unknown. In addition, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 82 publications
(109 reference statements)
6
51
0
Order By: Relevance
“…For the two whiteflies, gene rrnS is immediately followed by rrnL , with no transfer RNA gene but a long non coding sequence (94 and 53 bp) between them. However, the other whiteflies have one or more transfer genes between the two rRNAs [21,22,23,24,27]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the two whiteflies, gene rrnS is immediately followed by rrnL , with no transfer RNA gene but a long non coding sequence (94 and 53 bp) between them. However, the other whiteflies have one or more transfer genes between the two rRNAs [21,22,23,24,27]. …”
Section: Resultsmentioning
confidence: 99%
“…Family Aleyrodidae, with around 1450 named species, belongs to the order Hemiptera and comprise a single superfamily, Aleyrodoidea, within the suborder Sternorrhyncha [20]. Recent studies showed that mt genome of whiteflies have numerous gene rearrangements and transfer RNA gene absences [21,22,23,24]. Transposition of gene block cox3 - trnG - nad3 and the position of trnY and trnC are typical in whitefly mt genomes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the complete mtDNA genome (mtGenome) of only one invasive Bemisia species (i.e. the true B. tabaci ) MED are publicly available …”
Section: Introductionmentioning
confidence: 99%
“…This species is particularly harmful in tropical and subtropical areas, where currently B. tabaci is known as a complex composed of cryptic species (Wang et al, 2013;Marubayashi et al, 2013;Boykin, 2014;Barbosa et al, 2014). Bemisia tabaci damages plants by direct feeding and transmission of Begomoviruses and Criniviruses that cause serious problems due to viral epidemics (Morales, 2007;Marubayashi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%